Human Security Perspective Analysis through the Role of P4MI Madiun in Pre-Placement Protection of Taiwanese Migrant Workers in 2024 - Nadhif Samsul Ulum, Mohammad; Rohman, Abid (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The disparity between stages in legislation and practice in the field poses a challenge to the pre-placement protection process for Taiwanese migrant workers, which has significant relevance to the concept of human security. This study examines the role of P4MI Madiun in the pre-placement protection of Taiwanese migrant workers in 2024, grounded in the concept of human security. The purpose of this study is to gain a deeper understanding of the role of P4MI Madiun in the pre-placement protection of Taiwanese migrant workers in 2024. This study employs a descriptive qualitative method, utilizing primary data collected through interviews and the official website of P4MI Madiun, as well as prospective migrant workers. The results of this study indicate that the pre-placement protection provided by P4MI Madiun aligns with the concept of human security, particularly in terms of economic, health, and personal security. This study concludes that P4MI has fulfilled its duties as an implementer of UUPPMI through the pre-placement protection process for Taiwanese migrant workers in 2024.